Structural and electrochemical studies of undoped and In3+-doped co-binary Cu2-xTe and Bi2Te3 thin films for aqueous Na–S batteries - Sreerung, Rawita; Raknual, Duanghatai; Vailikhit, Veeramol; Teesetsopon, Pichanan; Kitisripanya, Nareerat; Tubtimtae, Auttasit (My University, 2019)
WO3 electrodes coated with co-binary Cu2-xTe and Bi2Te3 thin films were fabricated for sodium-sulfur (Na–S) batteries. Film fabrication was controlled by adjusting the pH of the solution and the indium doping concentration. The phases of orthorhombic CuTe and hexagonal Cu2Te with rhombohedral Bi2Te3 were formed on the WO3 electrode. After In3+ doping, In3+ ions act as Frenkel defects in the Cu2-xTe structure. This indicated that In3+ ions are located at interstitial sites in the Cu2-xTe structure with higher defect creation energy. Furthermore, more interconnected-like nanoparticles and reduced porosity were observed, thereby indicating that indium segregation with grain boundaries presented and contributed to an enhancement of the surface mobility, nucleation density, and a smoother surface. For electrochemical characteristics, a polysulfide solution was used as a redox electrolyte for ion transport. Optimization of the pH and indium concentration attributed to improve the exchange current density (J0) and time responses for the colored and bleached states because of faster movement of Na+ and S2− ions during inter/de-intercalation. Furthermore, optimization of the electrode by adjusting the pH and doping with indium is advantageous for both Na–S and rechargeable batteries because of long life cycle, reasonably high power and energy density of 306 W/kg and 9.35 Wh/kg, respectively. The highest specific capacity (Cs) values of the charge and discharge cycles for In3+-doped electrodes are ∼ 21 and 19 mAh/g, respectively with the coulombic efficiency approximates 100% (average value of ∼96%). This approach may provide a general path for the fabrication of undoped and In3+-doped co-binary Cu2-xTe and Bi2Te3 films on WO3 electrodes and may increase our knowledge regarding Na–S batteries for further performance improvement.
Keywords: Cu2-xTe/Bi2Te3 thin film; Electrochemical performance; Indium doping; Na–S battery; pH adjustment